Analisis Kepuasan Konsumen Ditinjau dari Fitur Marketplace dan Pengalaman Belanja pada Pengguna Shopee di Kabupaten Purworejo - Riski Nur Wulandari; Dewi Shanti Nugrahani; Hesti Respatiningsih (CV. ALIM'SPUBLISHING, 2026)
This study aims to examine the influence of service features and shopping experiences on Shopee customers' satisfaction, particularly among users in Purworejo Regency. This study employed a quantitative approach using a survey method. Data were collected by distributing questionnaires to 97 respondents selected through a purposive sampling technique. The collected data were analyzed using multiple linear regression, t-test, and F-test with IBM SPSS version 26. The results indicated that both service features and shopping experiences have a positive and significant influence on customer satisfaction, both partially and simultaneously. These findings suggest that well-designed marketplace features, such as ease of navigation, secure payment systems, and efficient transaction processes, combined with positive shopping experiences, play an important role in enhancing customer satisfaction. A satisfying shopping experience encourages customers to develop positive perceptions of the platform and increases the likelihood of repeated use and customer loyalty. Therefore, Shopee should continue to improve the quality of its digital services while maintaining a seamless and enjoyable shopping environment. This research contributes to the literature on E-commerce consumer behavior and can serve as evaluation material for the Shopee marketplace in developing strategies to improve customer satisfaction and maintain competitiveness in the digital marketplace.